Northern Shrimp (Pandalus borealis) on Flemish Cap in July 2001 - Díaz, Paz (Northwest Atlantic Fisheries Organization, 2001)
18 páginas, 7 figuras, 8 tablas.-- Scientific Council Meeting Results on shrimp from the survey on Flemish Cap in 2001 are presented and compared to those from previous surveys of the same series. The female biomass remains at a high level, and it is dominated by age 4 shrimp. A comparative trial between the Lofoten gear, the one used in the survey series, and a Campelen gear, indicates that the catch in weight of shrimp is around 7 times bigger in the second gear. The Campelen gear also catches large amounts of small shrimp due to its smaller cod-end mesh size. The European Commission (DG XIV, Study 00-028) and CSIC supported this study Peer reviewed